Support for the functioning of the gas turbine cogeneration system on biogas fuele - Chaikovskaya, Eugene (Видавництво Львівської політехніки, 2018)
The structural scheme of maintenance of the network water temperature in the conditions of operation of the gas turbine cogeneration system on biogas fuel with the use of a heat pump for which a fermented wort is a low-energy source of energy is proposed. Making decisions on the change of the number of plates of the heat utilizer when measuring the temperature of the gases at the inlet to the heat utilizer and the temperature of the return water allows, for example, to operate a cogeneration system with a capacity of 65.5 MW to reduce the cost price of the produced energy to 20-30%.
Keywords: Operation support; cogeneration system; decision making; 621.31